Penyuluhan Gejala Defisiensi Unsur Hara Pada Tanaman Kelapa Sawit Dan Pengendalian Organisme Pengganggu Tanaman Di Desa Sungai Majo Kecamatan Kubu Kabupaten Rokan Hilir - M. Amrul Khoiri; Zafitra Zafitra; Joni Irawan; Riskia Trizayuni; Besri Nasrul; Sri Yoseva; Heralda Fawrin; Purwasandi Purwasandi (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2025)
This extension activity was carried out in Sungai Majo Village, Kubu Sub-district, Rokan Hilir Regency with the objective of enhancing the knowledge and skills of oil palm farmers in recognizing nutrient deficiency symptoms and implementing strategies for plant pest organism control. The methods applied included lectures, participatory discussions, and field demonstrations. The materials delivered covered the identification of nutrient deficiency symptoms of both macro and micro elements, such as nitrogen (N), phosphorus (P), potassium (K), magnesium (Mg), and boron (B), along with their implications for plant growth and productivity. In addition, information was provided on common PPOs found in oil palm plantations and appropriate control techniques based on the principles of integrated crop management. The evaluation results showed an increase in farmers' understanding of nutrient deficiency symptoms from 30% before the activity to 75% after the activity, as well as an increase in understanding of OPT control from 40% to 70%. More than 80% of participants were able to independently identify symptoms of K and Mg deficiencies, and 75% of participants understood balanced fertilization techniques according to recommendations. Farmers also became more capable of recognizing pest attacks and understood environmentally friendly control alternatives, including mechanical, cultural, and biological approaches. Overall, this activity contributed to strengthening farmers’ capacity in sustainable oil palm management.